PERAN PSIKOLOGI PERKEMBANGAN DALAM DUNIA PENDIDIKAN ANAK SMP - Sianturi, Novita Perdamean; Diarang, Ayudhia; Loho, Heskia; Rasjid, Aprilia (PADAMARA: Jurnal Psikologi dan Sosial Budaya, 2024)
This article discusses the importance of developmental psychology in the education of junior high school children, who are in the age range of 10 to 14 years old. Psychology, derived from the words "psyche" (soul) and "logos" (science), is a field that investigates the mental processes, actions and behaviors of humans in relation to their environment. Developmental psychology specifically studies mental and behavioral changes throughout an individual's life. A deep understanding of developmental psychology is essential for educators and parents of middle school children, in order to understand and respond to their physical, cognitive, social, and emotional developmental needs. The methodology used in this study is the desk research method, which involves collecting and analyzing data from various literature sources such as reference books, articles, and journals. Through this method, the researcher identified important ideas, principles, and perspectives relevant to the topic. The research findings show that developmental psychology plays a vital role in the education of middle school children. Educators need to understand children's developmental phases in order to design appropriate learning programs, as well as identify and address developmental issues that may arise. The main challenges in the developmental process of middle school children include the development of technology and social media, academic pressure, media influence, and mental health issues. The proposed solutions include digital education, study time management, emotional support, monitoring social media use, anti-cyberbullying programs, and access to mental health services. Thus, applying the principles of developmental psychology in the education of junior high school children can create a learning environment that supports physical, emotional, and social development, and produce a quality generation. Collaboration between educators, psychologists and parents is essential to achieve this goal.